Identification of anise (Anisum vulgare Gaertn.) herbs by morphological and anatomical characteristics - S. V. Kolisnyk; T. M. Gontova; U. A. Umarov; K. R. Hordiei (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2021)
The fruits of anise contain different classes of biologically active compounds, due to which they have antidepressant, antiperoxidant, antidiabetic effect; extracts of this plant have an antibacterial effect. Professional literature lacks information on the chemical composition of anise herbs and prospects for their use in medicine.